Comunidade de macroinvertebrados bentônicos do rio Madeira e tributários no trecho de construção da UHE Santo Antônio do Madeira, Rondônia, Brasil - Nunes, Marcos Vinicius (Universidade Federal de São Carlos, 2016)
The construction of hydroelectricity power plants in lotic systems promote changes in the morphological and functional characteristics of these ecosystems, also leading to changes in the structure and dynamics of biological communities, both, qualitative and quantitative. Among the communities usually inhabiting recently created reservoirs, benthic macroinvertebrates have special relevance for having close relationship with environmental factors, simultaneously and differently responding to environmental changes. Therefore, based on the hypothesis that the structure and composition of benthic community might be altered as a consequence of the river damming, the presente work had as its main objective to make a species inventory occurring in a stretch of the Madeira River, before and after the construction of the UHE de Santo Antônio do Madeira, determining the composition and spatial di stribution of Hirudinea assemblages, verifying if the Oligochaeta species associatins in Madeira River are similar to those found in other large South America rivers, and if the construction of the power plant altered the patterns of association and distribution of species. Besides that Chironomidae assemblages were analyzed aiming to see if they were also affected, looking at their responses evaluated by biological indices considering the environmental changes after river damming. For this, sediment samples were collected for benthic macroinvertebrates analyses in eight sampling points, being six located upstream the dam and two downstream, before and after damming. Water variables were in situ measured: pH, electrical conductivity, dissolved oxygen, turbidity and temperature, and the sediment collected for granulometric analyses and nutrient concentrations measurements. The results obtained showed that both, water variables and sediment size-fractions were altered in some localities influencing leeches assemblage composition and abundances. It was also observed that Oligochaeta assemblage had a pattern of species association and that it does not tend to disappear after the river damming. However, the river damming caused changes in the structure and composition of the populations of Chironomidae. A decrease in the richness of taxa and overall changes in the benthic community before and after damming was also observed, thus evidencing that dam construction acted as a controlling factor of benthic community. Although the taxonomic richness and diversity index have not responded to these changes, contrarily the β diversity and the relationship between diversity and abundance of classes were sensitive to changes caused by the damming.
Keywords: Invertebrados; Usina hidrelétrica; Mudanças ambientais; Rios amazônicos; Invertebrates; Hydropower; Environmental changes; Amazonian rivers; CIENCIAS BIOLOGICAS